GEOMORPHOLOGICAL CHANGES IN THERMAIKOS GULF REGION AS A RESULT OF THE HOLOCENE SEA LEVEL RISE - ΑΛΜΠΑΝΑΚΗΣ, Κ.; ΣΤΥΛΛΑΣ, Μ.; ΒΟΥΒΑΛΙΔΗΣ, Κ.; ΣΥΡΙΔΗΣ, Γ. (Bulletin of the Geological Society of Greece, 2005)
Thermaikos Gulf receives sediment fluxes from major rivers at its western side, where a thick Holocene deltaic sequence has been developed. The eastern site of the gulf is characterized by alternating erosional and depositional coastlines with the formation of marine terraces and lagoons respectively. Application of the Bruun equilibrium profile model to eastern side of the gulf indicated that the terraces are retreating with high rates of erosion in response to Holocene sea level rise. The mean retreat rate is approximately 0.15 m/y for the last 10000 years, but the recent rate must be lower at about 0.10 m/y. Significant part of the ancient town Aineia, which was build on the eroding terrace, has already been disappeared. The recent low depositional coastlines with lagoons are found in the axis of old valleys, where depositional processes created low morphological profile, which is in equilibrium with the wave processes, according to Bruun model. The recent form of eastern Thermaikos coastline, where the low coastal areas form headlands is the result of faster re-treat of coastal terraces, leaving the depositional low coastal regions as promontories.